(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study examined the impact of fiscal policy on Ghana’s economic growth and development, focusing on the period from 2010 to 2019. Using an Ex-post facto research design and Ordinary Least Square (OLS) regression model, the investigation evaluates the influence of fiscal policy instruments, specifically tax revenue and government expenditure, on economic growth represented by GDP and infrastructural development (INDF). Findings show a strong correlation between fiscal policy instruments and GDP, indicating a significant impact of fiscal policy on Ghana’s economic growth. In contrast, while fiscal policy instruments demonstrated a moderate positive correlation with infrastructural development, they did not show a statistically significant impact, suggesting other factors might also considerably influence INDF. However, when considering tax revenue alone, a statistically significant impact on infrastructural development was observed. The results underscore the need for sound fiscal policies to drive economic growth, as effective government expenditure and tax revenue management could foster a conducive environment for GDP growth.